Virulent Type A Francisella tularensis actively suppresses cytokine responses in human monocytes - Gillette, Devyn D.; Curry, Heather M.; Cremer, Thomas; Ravneberg, David; Fatehchand, Kavin; Shah, Prexy A.; Wewers, Mark D.; Schlesinger, Larry S.; Butchar, Jonathan P.; Tridandapani, Susheela; Gavrilin, Mikhail A. (Frontiers in Cellular and Infection Microbiology, 2014)
Francisella tularensis is a Gram-negative facultative bacterium that can cause the disease tularemia, even upon exposure to low numbers of bacteria. One critical characteristic of Francisella is its ability to dampen or subvert the host immune response. Previous work has shown that monocytes infected with highly virulent F. tularensis subsp. tularensis strain Schu S4 responded with a general pattern of quantitatively reduced pro-inflammatory signaling pathway genes and cytokine production in comparison to those infected with the less virulent related F. novicida. However, it has been unclear whether the virulent Schu S4 was merely evading or actively suppressing monocyte responses. By using mixed infection assays with F. tularensis and F. novicida, we show that F. tularensis actively suppresses monocyte pro-inflammatory responses. Additional experiments show that this suppression occurs in a dose-dependent manner and is dependent upon the viability of F. tularensis. Importantly, F. tularensis was able to suppress pro-inflammatory responses to earlier infections with F. novicida. These results lend support that F. tularensis actively dampens human monocyte responses and this likely contributes to its enhanced pathogenicity.